Diagnosing Hodgkin Lymphoma From an Endobronchial Ultrasound Core Needle Biopsy. Issue 4 (October 2016) - Furukawa, Brian S.; Bernstein, Matthew; Siddiqi, Nasar; Pastis, Nicholas J.
Abstract : Hodgkin lymphoma (HL) commonly presents as isolated mediastinal adenopathy. Although there is evidence to support minimally invasive techniques such as endobronchial ultrasound (EBUS) fine-needle aspiration as the initial diagnostic test for suspected lymphoma involving the mediastinum, it consistently performs the poorest at definitively diagnosing HL for a variety of reasons, and therefore histology specimens are usually required. We present a case of HL presenting as isolated mediastinal adenopathy that was definitively diagnosed on EBUS using a 22 G coring needle in which cellular and histologic specimens were obtained, allowing the core biopsy to be fixed in formalin and treated as a surgical specimen. The patient started treatment soon after the procedure without requiring any further invasive tests. Although it seems intuitive that a coring EBUS needle would be advantageous in diseases such as HL, further studies are needed before definitive recommendations can be made.